ANALISIS PENGARUH INVESTASI,EKSPOR DAN TENAGA KERJA TERHADAP PDRB DALAM KAWASAN EKONOMI KHUSUS (KEK) DI KABUPATEN KOTABARU - MUHAMMAD TAUFIQ RAHMAN; YUNITA SOPIANA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
M.Taufiq Rahman (2019), Analysis of the Effect of Investment, Exports and Labor on GRDP in Special Economic Zones in Kotabaru Regency            The background of this research is that the special economic zone policy is expected to be able to increase the value of investment, exports and labor. With the increase in these three sectors, it will be able to drive the rate of economic growth and increase the value of GDP.            The benefit of this research is to provide information related to the investment, export and labor sectors in contributing to the Kotabaru district GRDP value. and this research can provide understanding to the regional government, the developer and community institutions with an interest in developing special economic zones in Mekar Putih, Kotabaru Regency. where this research can be a reference in the preparation of strategic plans in the development of Special Economic Zones in Mekar Putih Kotabaru Regency            This research method uses the method of collecting data by retrieving data at the related statistical and service centers. after that multiple linear regression analysis was carried out to see the magnitude of the influence of independent variables on dependent. Software used for regression analysis is using Eviews            The results of the analysis of this study indicate that investment has a significant effect and has a positive influence on GDP while exports and labor do not have a significant effect but still have a positive influence on the GDP of Kotabaru Regency.key words: Special Economic Zones, Investment, exports, Labor